2015
DOI: 10.2174/1381612821666150115125717
|View full text |Cite
|
Sign up to set email alerts
|

Material Couture for Wound Healing and Regeneration: an Overview

Abstract: Wound healing is a complex regenerative process of great importance in clinical medicine, controlled by temporal interactions between cells, extracellular matrix components and signalling molecules. Localised delivery of therapeutic active agents viz. antimicrobials, soothing minerals and/or vitamins and growth factors at the site of injury/trauma/wound are expected to be more effective and will always manifest milder toxic concerns than those observed upon systemic administration of these agents. Since ancien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Thermoplastic polyurethane (TPU) is a biocompatible and biodegradable elastomer that has been approved by the FDA, and has been widely applied in biomedical science [ 9 , 10 ]. It has been reported that TPU can be used for catheters, vascular grafts and drug delivery carriers [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermoplastic polyurethane (TPU) is a biocompatible and biodegradable elastomer that has been approved by the FDA, and has been widely applied in biomedical science [ 9 , 10 ]. It has been reported that TPU can be used for catheters, vascular grafts and drug delivery carriers [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that TPU can be used for catheters, vascular grafts and drug delivery carriers [ 11 13 ]. Moreover, TPU also exhibits remarkable chemical stability and good mechanical properties [ 10 , 12 ]. These superior performances indicate that TPU is a promising candidate for wound dressings.…”
Section: Introductionmentioning
confidence: 99%
“…For wound dressing materials, natural and synthetic polymers are commonly used as the dressing material, in the form of films, hydrogels, and scaffolds [ 29 ]. Recently, natural materials have gained much attention in biomedical production because of their high biocompatibility and environmentally friendly properties [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, various dressing materials such as grease, honey, and oil were used to cover wounds to prevent infection and/or reduce pain . A material that protects the wound while promoting wound healing is clinically advantageous . Thus, various such dressing materials have been developed and clinically applied .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 A material that protects the wound while promoting wound healing is clinically advantageous. [3][4][5][6][7][8] Thus, various such dressing materials have been developed and clinically applied. 9 For example, collagen, an abundant extracellular matrix component, in combination with a thin silicone sheet is clinically applied to burns, traumas, and surgically operated wounds.…”
Section: Introductionmentioning
confidence: 99%